Большая книга Рождества, составленная Наталией Будур и Иваном Панкеевым - Будур Наталия (ОЛМА-ПРЕСС, 2000)
Экземпляры: (20180115) / Инвентарный номер: 26463 / Цена: 75.00 / Сис.шифр: 74.9 / Авт.знак: Б 79 / ББК: 74.9